New Prionospio and Aurospio Species from the Deep Sea (Annelida: Polychaeta) - Paterson, Gordon L. J.; Neal, Lenka; Altamira, Iris; Soto, Eulogio H.; Smith, Craig R.; Menot, Lenaick; Billett, David S. M.; Cunha, Marina R.; Marchais-Laguionie, Clare; Glover, Adrian G. (Zootaxa, 2016)
The number of records of the genus Prionospio Malmgren, 1867, from the deep sea (>2000 m) are relatively few and do not reflect the actual occurrence of species nor their potential ecological importance. In this paper we describe five new species of this genus (Prionospio amarsupiata sp. nov., P. vallensis sp. nov., P. branchilucida sp. nov., P. hermesia sp. nov. and P. kaplani sp. nov.) all of which are abundant members of the deep-sea community. We also describe two new species of the genus Aurospio Maciolek, 1981 (Aurospio abranchiata sp. nov. and A. tribranchiata sp. nov.) again common elements of the abyssal fauna. Two of the new species have characters which question the generic distinctiveness of Prionospio and Aurospio. The problems in differentiating these two genera are discussed.
World Polychaeta Database (WPolyDb)